Os cultos de Ísis e Atargátis no alto Império Romano: conflito religioso e formação de identidades nas Metamorphoses e De Dea Syria - Soares, Hariadne da Penha (2011)
Present in this dissertation a study of religious conflicts among devotees of pagan deities Isis and Atargatis, also known as Goddess Syria and its interrelation with the Roman social life during the High Empire. What concerns explored Eastern religions and the conflicts between the various religions present in the pagan Roman Empire. We used two sources as very important works: the De Dea Syria, Lucian of Samosata and work Metamorphoses of Apuleius of Madaura. We assume that the orientalization of the Roman Empire, viewed as a process of gradual integration of deep and ancient customs absorbed with the cultural heritage of the East resulted in some circumstances, the adoption of a derogatory speech against religious rivals, as we see in case of conflict between the devotees of Isis and of Atargatis, suggesting to us so even among the heathen is possible to detect focuses of intolerance and religious discrimination, as well as the formation of ethnic and religious identity in Roman high society Imperial.